The Kinase STATE TRANSITION 8 Phosphorylates Light Harvesting Complex II and Contributes to Light Acclimation in Arabidopsis thaliana - Longoni, Paolo; Samol, Iga; Goldschmidt-Clermont, Michel (Frontiers in Plant Science, 2019)
Phosphorylation of the light-harvesting complex II (LHCII) is a central trigger for the reorganization of the photosynthetic complexes in the thylakoid membrane during short-term light acclimation. The major kinase involved in LHCII phosphorylation is STATE TRANSITION 7 (STN7), and its activity is mostly counteracted by a thylakoid-associated phosphatase, PROTEIN PHOSPHATASE 1/THYLAKOID ASSOCIATED PHOSPHATASE 38 (PPH1/TAP38). This kinase/phosphatase pair responds to the redox status of the photosynthetic electron transport chain. In Arabidopsis thaliana, Lhcb1 and Lhcb2 subunits of the LHCII trimers are the major targets of phosphorylation and have different roles in the acclimation of the photosynthetic machinery. Another antagonistic kinase and phosphatase pair, STATE TRANSITION 8 (STN8) and PHOTOSYSTEM II PHOSPHATASE (PBCP) target a different set of thylakoid proteins. Here, we analyzed double, triple and quadruple knock-out mutants of these kinases and phosphatases. In some of these mutants, lacking STN7 but not STN8, the phosphorylation of LHCII was partially restored. In contrast to phosphorylation of LHCII by STN7, its phosphorylation by STN8 did not respond to the redox status of the electron transport chain. The recovered phosphorylation favors Lhcb1 over Lhcb2 and results in a better adaptation of the photosynthetic apparatus and increased plant growth under fluctuating light. This set of mutants allowed to unveil a contribution of STN8-dependent phosphorylation in the acclimation to rapid light variations.